2023
DOI: 10.3390/ani13132076
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Atomization of Ketamine, Medetomidine and Butorphanol in Pet Rabbits Using a Mucosal Atomization Device

Abstract: A non-invasive method of drug delivery, intranasal atomization, has shown positive results in human medicine and in some animal species. The objective of this study was to evaluate the effects of intranasal atomization, compared to intramuscular administration, of a mix of anesthetic drugs in pet rabbits. In total, 104 mixed-breed pet rabbits, undergoing various types of surgery, received a combination of ketamine, medetomidine, and butorphanol (20, 0.4, and 0.2 mg/kg) by intranasal atomization using a Mucosal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This suggests that, nonetheless, the anesthesiological protocol used would have been adequate for the surgical procedure, ensuring anesthetic stability. In our study, the choice of using a Mucosal Atomization Device to administer the anesthetic drug combination was made, as it was found to produce a lighter anesthetic plane compared to intramuscular administration of the same combination, resulting in faster recovery [16]. A relatively light anesthetic plan would have allowed for a more effective detection of a response to the surgical stimulus in the subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that, nonetheless, the anesthesiological protocol used would have been adequate for the surgical procedure, ensuring anesthetic stability. In our study, the choice of using a Mucosal Atomization Device to administer the anesthetic drug combination was made, as it was found to produce a lighter anesthetic plane compared to intramuscular administration of the same combination, resulting in faster recovery [16]. A relatively light anesthetic plan would have allowed for a more effective detection of a response to the surgical stimulus in the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol was approved by the Ethical committee of the Department of Veterinary Science of the University of Turin, protocol n. 0004179/2022. Power of 0.80, alpha error of 0.05, and 25% increase in mean heart rate (set at 160 ± 30 beats/min, based on the mean heart rate after anesthetic induction in rabbits using the same protocol as this study [16]; see Supplementary Materials) in non-treated animals compared to treated ones were considered for sample size calculation. Results indicated that the use of at least 18 rabbits (9 per group) would prevent a type II error (www.clincalc.com, accessed on 10 November 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, in addition to ketamine and medetomidine, butorphanol was utilized as part of the anesthesiological protocol. This molecule is commonly deemed safe when applied in rabbit anesthesia, with few adverse effects [ 13 , 20 ]. One study reported a temporary reduction in gastric motility following the administration of 10 mg kg −1 of butorphanol intramuscularly [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…To induce anesthesia, a combination of 20 mg kg −1 ketamine (Ketavet 100, MSD Animal Health S.r.l., Segrate, Milan, Italy), 0.4 mg kg −1 medetomidine (Medeson, Industria Italiana Integratori Trei S.p.A., Livisto, Rio Saliceto, Reggio-Emilia, Italy), and 0.2 mg kg −1 butorphanol (Nargesic ® 10 mg/mL, Acme S.r.l., Corte Tegge-Cavriago, Reggio-Emilia, Italy) was intramuscularly administered to all subjects [ 20 ]. After the loss of the righting reflex, each rabbit was positioned on a heating pad in dorsal recumbency and connected to a multiparameter monitoring system (Infinity Delta ® , Dräger Italia S.p.A., Corsico, Italy) to monitor vital parameters via electrocardiography and pulse oximetry.…”
Section: Methodsmentioning
confidence: 99%